(untitled) (Research, Society and Development, 2020)
The aim of this study is to identify the most frequent feelings and reactions of mothers who experienced pregnancy loss, and to understand the contribution of psychotropic drugs to women in the face of the contained mourning process. It is an integrative literature review, with a qualitative approach, carried out by searching for articles indexed in the Virtual Health Library (VHL), with the help of the following databases: Scientific Electronic Library Online (SCIELO), National Center for Biotechnology Information (PUBMED), Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF), and Electronic Journals in Psychology (PEPSIC). The inclusion criteria include literature review surveys available in the databases described, between the years 2010 to 2020. As exclusion criteria, articles were not considered for monetary compensation, incomplete and not converging with this study. To survey the data and composition of this study, 11 articles were analyzed. The results show the most frequent feelings of women in mourning contained after the pregnancy loss, and the implementation of the use of psychotropic drugs to deal with the experience of mourning. Thus, we conclude that the feelings and reactions of these women in the face of the grieving process, the phases of grief, the externalization of the various disturbing emotions, result in the search for psychotropic drugs to alleviate the sensations experienced in this process.